The Transformative Role of Augmented Reality in E-Commerce: A Mixed-Methods Study on Consumer Trust Across Cultural Contexts - -, Wawah Sri Sunenti; Santoso, Joseph Teguh (Benefit: Jurnal Manajemen dan Bisnis, 2025)
Augmented Reality (AR) is becoming increasingly influential in global e-commerce, especially in how it helps narrow the gap between digital and physical shopping experiences. This study explores AR’s role in shaping consumer trust, not only during initial interactions but also over time, across different cultural settings. By combining structured surveys (N = 200) and qualitative interviews, this research uses a mixed-methods design to understand behavior patterns and how trust is built. Results show that higher content frequency (r = 0.72, p = 0.001) links strongly to engagement, while both social media (β = 0.47, p < 0.001) and content marketing (β = 0.31, p < 0.001) also play major roles. In the qualitative analysis, participants often highlighted that using multiple platforms, offering personalized content, and being sensitive to culture helped maintain trust over time.